Pesticides in human milk of Western Australian women and their influence on infant growth outcomes: A cross-sectional study. (January 2017) - Du, Jian; Gridneva, Zoya; Gay, Melvin C.L.; Trengove, Robert D.; Hartmann, Peter E.; Geddes, Donna T.
Abstract: Persistent organic pollutants in human milk (HM) at high levels are considered to be detrimental to the breastfed infant. To determine the pesticide concentration in HM, a pilot cross-sectional study of 40 Western Australian (WA) women was carried out. Gas chromatography-tandem mass spectrometry (GC-MS/MS) with a validated QuEChERS was used for the analysis of 88 pesticides in HM. p, p′- dichlorodiphenyldichloroethylene ( p, p′ -DDE) with a mean concentration of 62.8 ± 54.5 ng/g fat was found, whereas other organochlorines, organophosphates, carbamates and pyrethroids were not detected in HM. Overall, no association was observed between HM p, p′ -DDE concentrations and maternal age, parity, body mass index and percentage fat mass. Furthermore, for the first time no significant association was found between p, p′ -DDE concentrations in HM and infant growth outcomes such as weight, length, head circumference and percentage fat mass. The calculated daily intake was significantly different to the estimated daily intake of total DDTs and was well below the guideline proposed by WHO. The DDTs levels in WA have also significantly decreased by 42 - fold since the 1970s and are currently the lowest in Australia. Highlights: Cross-sectional study of 88 POPs in human milk over first year of lactation. p, p′ -DDE was detected in 87.5% of the human milk samples. No significant associations between p, p′ -DDE and infant growth outcomes. Estimated daily intake overestimates human milk POP concentration. Human milk infant intake of DDTs is below the recommended daily intake guidelines.